Production of l -Theanine by Escherichia coli in the Absence of Supplemental Ethylamine - Hagihara, Ryota; Ohno, Shoto; Hayashi, Mikiro; Tabata, Kazuhiko; Endo, Hirofumi (Applied and environmental microbiology, 2021)
l -Theanine is widely used in food additives and dietary supplements. Industrial production of l -theanine uses the toxic and highly flammable precursor ethylamine, raising production costs. In this study, we used Escherichia coli to engineer two biosynthetic pathways that produce l -theanine from glucose and ammonia in the absence of supplemental ethylamine. This study establishes a foundation for safely and economically producing l -theanine.